Contemporary evolution of host plant range expansion in an introduced herbivorous beetle Ophraella communa. (22nd January 2016) - Fukano, Y.; Doi, H.; Thomas, C. E.; Takata, M.; Koyama, S.; Satoh, T.
Abstract: Host range expansion of herbivorous insects is a key event in ecological speciation and insect pest management. However, the mechanistic processes are relatively unknown because it is difficult to observe the ongoing host range expansion in natural population. In this study, we focused on the ongoing host range expansion in introduced populations of the ragweed leaf beetle, Ophraella communa, to estimate the evolutionary process of host plant range expansion of a herbivorous insect. In the native range of North America, O. communa does not utilize Ambrosia trifida, as a host plant, but this plant is extensively utilized in the beetle's introduced range. Larval performance and adult preference experiments demonstrated that native O. communa beetles show better survival on host plant individuals from introduced plant populations than those from native plant populations and they also oviposit on the introduced plant, but not on the native plant. Introduced O. communa beetles showed significantly higher performance on and preference for both introduced and native A. trifida plants, when compared with native O. communa . These results indicate the contemporary evolution of host plant range expansion of introduced O. communa and suggest that the evolutionary change of both the host plant and the herbivorous insect involved in the host range expansion.